Mathematical Modeling of the Reinforcing the Profitability of Traditional Markets - Netriwati, Netriwati; Qulyasry, Fadila; Nabila, Siti Ulfa; Nendra, Fadly; Sari, Meta (Universitas Sang Bumi Ruwa Jurai, 2025)
This study aims to develop a mathematical model to analyze the impact of the revitalization program at Koga Market, Bandar Lampung, on traders’ profits by examining the influence of sales volume, marketing costs, staple-goods prices, and infrastructure costs. Using a quantitative survey approach involving 50 randomly selected traders, data were collected through questionnaires, interviews, and documentation, and analyzed using descriptive statistics, classical assumption tests, and multiple linear regression. The results show that staple-goods prices and infrastructure costs have a strong and significant positive effect on traders’ profits, marketing costs also contribute positively, while sales volume shows a negative but insignificant effect. All classical assumptions were met, indicating that the regression model is valid for explaining the profit determinants. The findings confirm that market revitalization has generated measurable economic benefits through improved infrastructure and stable commodity prices, suggesting the need for continued infrastructure enhancement and strengthened marketing strategies to further support traders’ economic sustainability.